Teacher Roles and Elementary Students Learning Interest in Classroom Practice: Peran Guru dan Minat Belajar Siswa Sekolah Dasar dalam Praktik Pembelajaran - Karismah Nadia Amelia; Abdul Rahman; Nuraini Nuraini; Zulnuraini Zulnuraini; Ammar Abdullah Joni Guci (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Student learning interest is a crucial factor that supports active participation, attention, and enthusiasm during the learning process in elementary education. Specific Background: Teachers hold a central role in shaping classroom learning conditions and guiding students through various pedagogical responsibilities. Knowledge Gap: Although many studies discuss teacher roles in learning, contextual analysis focusing on the homeroom teacher’s roles in fostering learning interest among fourth-grade students remains limited. Aims: This study aims to analyze the roles of teachers in relation to the learning interest of fourth-grade students at Al-Khairaat Elementary School Tondo. Results: Using a descriptive qualitative approach involving one homeroom teacher and twenty-eight students, data collected through observation, interviews, and documentation reveal that teachers perform eight key roles: educator, learning resource, guide, classroom manager, demonstrator, motivator, facilitator, and evaluator. Empirical findings indicate that these roles are reflected through exemplary attitudes in teacher–student interactions, the use of instructional media such as videos and educational games, flexible classroom seating arrangements, and simple reward systems to encourage participation. Students showed varied levels of learning interest; however, most demonstrated increased activeness, attention, and enthusiasm when interactive and contextual learning strategies were implemented. Novelty: This study provides a contextual description of how the homeroom teacher’s multiple roles operate simultaneously in classroom practice to support student engagement. Implications: The findings suggest that adaptive and sustained implementation of teacher roles can serve as a practical strategy to cultivate elementary students’ learning interest according to classroom characteristics. Highlights • Classroom practice demonstrates eight integrated instructional roles performed by homeroom teachers.• Interactive strategies using media, contextual explanation, and rewards encourage student participation.• Student engagement increases when learning activities involve active interaction and contextual tasks. Keywords Teacher Roles; Learning Interest; Elementary Education; Classroom Learning; Student Engagement